Pengaruh Motivasi dan Kepemimpinan terhadap Disiplin Kerja dan Perilaku serta Kinerja Karyawan Sub Section Level pada PT. Bogasari Flour Mill - Koesmono, Teman (Jurnal Widya Manajemen & Akuntansi, 2005)
The purpose of this research is to find out the effect of organizational behavior factors on employees' performance. Organizational behaviors factors include are employee's motivation, leadership, working discipline, and behavior. This research's object is employees on subsection level in PT. Bogasari Flour Mill. PT. Bogasari Flour Mill was chosen as the place for this research because this company produces food ingredient that is exported, thus it gives a contribution in foreign exchange earning for the country. The result of this research can explain that motivation and leadership affect one's behavior, working discipline, and performance. Motivation and leadership patterns are very much needed to lead employee's behavior in order to generate the maximum performance. The more positive employee's behavior they get hopefully the faster the company's short/long term goal will be achieved. Along with the achievement the company's goal there will be an effect on improvement of employee's working satisfaction and welfare.